2020
DOI: 10.1002/jbt.22482
|View full text |Cite
|
Sign up to set email alerts
|

Troxerutin downregulates C/EBP‐β gene expression via modulating the IFNγ‐ERK1/2 signaling pathway to ameliorate rotenone‐induced retinal neurodegeneration

Abstract: Troxerutin, a natural flavonoid guards against oxidative stress and apoptosis with a high capability of passing through the blood‐brain barrier. Our aim was to investigate the role of troxerutin in experimentally induced retinal neurodegeneration by modulating the interferon‐gamma (IFNγ)‐extracellular signal‐regulated kinases 1/2 (ERK1/2)‐CCAAT enhancer‐binding protein β (C/EBP‐β) signaling pathway. Three groups of rats (10 each group) were included. Group I (control group), group II (rotenone treated group): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Recent in vitro experiments have shown that EGCG and its metabolites, such as theaflavins, can enter the brain parenchyma through the BBB, induce neuritogenesis and have a potential neuroprotective effect [20]. Troxerutin, a natural flavonoid with a high capability to pass through the BBB, can prevent rotenone-induced retinal neurodegeneration [21]. Quercetin, a flavonoid, has obvious neuroprotective effects on radioactive brain injury [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro experiments have shown that EGCG and its metabolites, such as theaflavins, can enter the brain parenchyma through the BBB, induce neuritogenesis and have a potential neuroprotective effect [20]. Troxerutin, a natural flavonoid with a high capability to pass through the BBB, can prevent rotenone-induced retinal neurodegeneration [21]. Quercetin, a flavonoid, has obvious neuroprotective effects on radioactive brain injury [22].…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of radioprotective products have been discovered, including polyphenols, anthocyanins, and polysaccharides. 18,29,30 In China, L. lancifolium Thunb . is widely grown for its edible bulbs, which is considered a vegetable with high nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are also anti-inflammatory scavengers of free radicals. Flavonoids are plant-derived compounds that exist naturally in various Chinese medicines, and exhibit radioprotective and neuroprotective properties [ 175 , 176 , 177 , 178 ]. Both flavonoids and their metabolites can cross the blood–brain barrier [ 179 ], which is composed of capillary endothelial cells, basement and neuroglial membranes, and glial podocytes [ 180 ], and approach brain cells to decrease brain injury, while improving neurodegenerative diseases and cognitive impairment [ 181 , 182 , 183 ].…”
Section: Biological Effects Of Microwavesmentioning
confidence: 99%